Contrasting patterns of population genomic structure between broadcast-spawning and brooding corals in Southeast Asia - Lutfi Afiq-Rosli; Benjamin J. Wainwright; Jen Nie Lee; Zarinah Waheed; Loke Ming Chou; Danwei Huang (Blackwell Publishing Inc., 2024)
Aim: As climate change increasingly threatens the world's coral reefs, enhancing their resilience by improving population connectivity for key reef species is crucial for ensuring their persistence. Here, we evaluate the population genomic structure of two common coral species, Pocillopora acuta and Porites sp., chosen due to their divergent life histories. Thousands of singlenucleotide polymorphisms (SNPs) were sequenced and analysed to infer regional connectivity patterns in Southeast Asia, a region that harbours a tremendous diversity of marine life. Location: Coasts of the Malay Peninsula and northern Borneo, covering ~1 million km2. Method: NextRAD genotyping-by-sequencing of 185 Porites sp. and 221 Pocillopora acuta colonies. Libraries were prepared and sequenced on Illumina NovaSeq 6000. Genotyping involved initial quality controls, allele frequency filtering and checks for contamination. Genetic structure was assessed with Bayesian clustering, and relationships between genetic variation and environmental factors were studied through redundancy analysis. Contemporary gene flow was estimated using BayesAss. Results: We observed panmixia among the broadcasting Porites sp. populations, while for the brooding Pocillopora acuta, the Malay Peninsula acts a strong barrier to dispersal between the Malacca Strait and the southern South China Sea. Moreover, its genomic structure seems to follow current marine ecoregion delineation. By analysing contemporary migrant movement, we can prioritise reef localities for conservation. In particular, localities at the Andaman Coral Coast are contemporarily isolated from the other localities, and Tioman is identified as a major larval source for both species. Main Conclusion: Our analyses highlight contrasting population differentiation patterns between the two species that can be explained by the disparity in their reproductive strategies. These findings are important for biodiversity managers in Southeast